The value of `lim_(h->0) (sin(pi+h) - sin pi)/h` has to be determined.

`lim_(h->0) (sin(pi+h) - sin pi)/h`

=> `lim_(h->0) (sin(pi+h) - 0)/h`

=>` lim_(h->0) (sin pi*cos h + cos pi*sin h - 0)/h`

=> `lim_(h->0) (0*cos h + (-1*sin h) - 0)/h`

=> `lim_(h->0) (-1*sin h)/h`

=>` -1*lim_(h->0) sin h/h`

=> -1

**The value of `lim_(h->0) (sin(pi+h) - sin pi)/h =
-1`**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.